Tingkat bahaya erosi daerah aliran sungai Tinalah Kabupaten Kulon Progo Daerah Istimewa Yogyakarta=The degree of erosion Hazard of Tinalah Watershed Kulon Progo district Yogyakarta Province - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
The objectives of the study are to know the erosion hazard using USLE, to study the gully erosion hazard using field measurement, and to evaluate the degree of surface and gully erosion hazard. The method applied was survey method with land unit approach. The land unit was prepared on the basis of overlaying the slope, soil, and landuse maps. The sampling method was stratified purposive, which consisted of variables comprising soil type, slope class, and landuse. Soil sampling was taken from 54 land units. Erosion hazard analysis was made using USLE from Wischmeir and Smith. The analysis of gully erosion hazard was conducted according to the density, the length, the width, and the depth of gullies. The erosion hazard classification of the surface erosion was made based on the Department of Forestry Republic of Indonesia. The result of this research showed that most of the surface erosion hazard in the Tinalah Watershed were low 1,621.4 ha (35.3%), very low 581.4 ha (12.6%), moderate 808.6 ha (17.6%), severe 790.2 ha (17.2%), and very severe 578.9 ha (12.6%). On the other hand, the rate of erosion occurred in the range of 0.2 up to 817.7 tones/ha/year. The gully erosion hazard in the Tinalah Watershed were very low 4,177.9 ha (72.4%), low 992.6 ha (17.2%), moderate 486.3 ha (8.4%), heavy 29.5 ha (0.5%). The rate of gully erosion occurred in the range of 0.04 tones/ ha up to 90.2 tones/ha. Based on the conservation type that was conducted on each land unit, the surface erosion hazard and the gully erosion hazard have been controlled either mechanically or vegetatively.